Discover a world of knowledge at Westonci.ca, where experts and enthusiasts come together to answer your questions. Join our platform to connect with experts ready to provide precise answers to your questions in various areas. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
To solve the polynomial equation [tex]\( x^4 - 3x^3 + 3x^2 - 3x + 2 = 0 \)[/tex], we need to find all the roots of the polynomial. Let’s go through the steps to find these roots analytically:
1. Write down the polynomial:
[tex]\[ f(x) = x^4 - 3x^3 + 3x^2 - 3x + 2 \][/tex]
2. Try to factor the polynomial:
One way to factorize a polynomial is to use the Rational Root Theorem, which suggests that potential rational roots are factors of the constant term (in this case, [tex]\(2\)[/tex]) divided by factors of the leading coefficient (which is [tex]\(1\)[/tex]).
The potential rational roots are [tex]\( \pm 1, \pm 2 \)[/tex].
3. Test potential rational roots:
Let's test [tex]\(x = 1\)[/tex]:
[tex]\[ f(1) = 1^4 - 3(1)^3 + 3(1)^2 - 3(1) + 2 = 1 - 3 + 3 - 3 + 2 = 0 \][/tex]
This indicates that [tex]\(x = 1\)[/tex] is a root.
Next, we use synthetic division or polynomial division to divide [tex]\(f(x)\)[/tex] by [tex]\(x - 1\)[/tex].
4. Perform polynomial division by [tex]\(x - 1\)[/tex]:
[tex]\[ x^4 - 3x^3 + 3x^2 - 3x + 2 \div (x - 1) \][/tex]
Using synthetic division:
[tex]\[ \begin{array}{r|rrrrr} 1 & 1 & -3 & 3 & -3 & 2 \\ & & 1 & -2 & 1 & -2\\ \hline & 1 & -2 & 1 & -2 & 0\\ \end{array} \][/tex]
The quotient is [tex]\(x^3 - 2x^2 + x - 2\)[/tex].
5. Repeat the process for [tex]\(x^3 - 2x^2 + x - 2\)[/tex]:
Test [tex]\(x = 1\)[/tex] for [tex]\(x^3 - 2x^2 + x - 2\)[/tex]:
[tex]\[ f(1) = 1^3 - 2(1)^2 + 1 - 2 = 1 - 2 + 1 - 2 = -2 \neq 0 \][/tex]
Test [tex]\(x = -1\)[/tex]:
[tex]\[ f(-1) = (-1)^3 - 2(-1)^2 + (-1) - 2 = -1 - 2 - 1 - 2 = -6 \neq 0 \][/tex]
Test [tex]\( x = 2\)[/tex]:
[tex]\[ f(2) = 2^3 - 2(2)^2 + 2 - 2 = 8 - 8 + 2 - 2 = 0 \][/tex]
This indicates [tex]\(x = 2\)[/tex] is a root.
6. Perform polynomial division by [tex]\(x - 2\)[/tex]:
[tex]\[ x^3 - 2x^2 + x - 2 \div (x - 2) \][/tex]
Using synthetic division:
[tex]\[ \begin{array}{r|rrrr} 2 & 1 & -2 & 1 & -2 \\ & & 2 & 0 & 2\\ \hline & 1 & 0 & 1 & 0\\ \end{array} \][/tex]
The quotient is [tex]\(x^2 + 1\)[/tex].
7. Solve the quadratic equation [tex]\(x^2 + 1 = 0\)[/tex]:
[tex]\[ x^2 + 1 = 0 \Rightarrow x^2 = -1 \Rightarrow x = \pm i \][/tex]
8. Combine all the roots found:
Therefore, the solutions to the polynomial equation are:
[tex]\[ \boxed{x = 1, x = 2, x = -i, x = i} \][/tex]
The correct choice is:
[tex]\[ x = \pm i, x = 1, x = 2 \][/tex]
1. Write down the polynomial:
[tex]\[ f(x) = x^4 - 3x^3 + 3x^2 - 3x + 2 \][/tex]
2. Try to factor the polynomial:
One way to factorize a polynomial is to use the Rational Root Theorem, which suggests that potential rational roots are factors of the constant term (in this case, [tex]\(2\)[/tex]) divided by factors of the leading coefficient (which is [tex]\(1\)[/tex]).
The potential rational roots are [tex]\( \pm 1, \pm 2 \)[/tex].
3. Test potential rational roots:
Let's test [tex]\(x = 1\)[/tex]:
[tex]\[ f(1) = 1^4 - 3(1)^3 + 3(1)^2 - 3(1) + 2 = 1 - 3 + 3 - 3 + 2 = 0 \][/tex]
This indicates that [tex]\(x = 1\)[/tex] is a root.
Next, we use synthetic division or polynomial division to divide [tex]\(f(x)\)[/tex] by [tex]\(x - 1\)[/tex].
4. Perform polynomial division by [tex]\(x - 1\)[/tex]:
[tex]\[ x^4 - 3x^3 + 3x^2 - 3x + 2 \div (x - 1) \][/tex]
Using synthetic division:
[tex]\[ \begin{array}{r|rrrrr} 1 & 1 & -3 & 3 & -3 & 2 \\ & & 1 & -2 & 1 & -2\\ \hline & 1 & -2 & 1 & -2 & 0\\ \end{array} \][/tex]
The quotient is [tex]\(x^3 - 2x^2 + x - 2\)[/tex].
5. Repeat the process for [tex]\(x^3 - 2x^2 + x - 2\)[/tex]:
Test [tex]\(x = 1\)[/tex] for [tex]\(x^3 - 2x^2 + x - 2\)[/tex]:
[tex]\[ f(1) = 1^3 - 2(1)^2 + 1 - 2 = 1 - 2 + 1 - 2 = -2 \neq 0 \][/tex]
Test [tex]\(x = -1\)[/tex]:
[tex]\[ f(-1) = (-1)^3 - 2(-1)^2 + (-1) - 2 = -1 - 2 - 1 - 2 = -6 \neq 0 \][/tex]
Test [tex]\( x = 2\)[/tex]:
[tex]\[ f(2) = 2^3 - 2(2)^2 + 2 - 2 = 8 - 8 + 2 - 2 = 0 \][/tex]
This indicates [tex]\(x = 2\)[/tex] is a root.
6. Perform polynomial division by [tex]\(x - 2\)[/tex]:
[tex]\[ x^3 - 2x^2 + x - 2 \div (x - 2) \][/tex]
Using synthetic division:
[tex]\[ \begin{array}{r|rrrr} 2 & 1 & -2 & 1 & -2 \\ & & 2 & 0 & 2\\ \hline & 1 & 0 & 1 & 0\\ \end{array} \][/tex]
The quotient is [tex]\(x^2 + 1\)[/tex].
7. Solve the quadratic equation [tex]\(x^2 + 1 = 0\)[/tex]:
[tex]\[ x^2 + 1 = 0 \Rightarrow x^2 = -1 \Rightarrow x = \pm i \][/tex]
8. Combine all the roots found:
Therefore, the solutions to the polynomial equation are:
[tex]\[ \boxed{x = 1, x = 2, x = -i, x = i} \][/tex]
The correct choice is:
[tex]\[ x = \pm i, x = 1, x = 2 \][/tex]
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.